Attributes of Biserrula pelecinus L. (biserrula): A new pasture legume for sustainable farming on acidic sandy soils in Mediterranean environments - Carr S.J.; Loi A.; Howieson J.H.; Porqueddu C. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Agricultural systems in Mediterranean southern Australia rely heavily on annual pasture legumes grown in rotation with cereals. Historically, Trifolium and Medicago have been the dominant genera, yet many soils are too acidic for the long term persistence of these genera, and their rhizobial microsymbionts. Serradella, a species symbiotic with acid soil tolerant Bradyrhizobia offers an alternate for acid soils, yet adoption by Australian farmers has been hampered by the expensive seed processing needed for serradella. In this paper, we discuss Biserrula pelecinus, a monotypic genus endemic to the Mediterranean basin with unique root-nodule bacteria. The agronomic adaptation of biserrula, and the ease of seed harvesting and processing compared with current pasture species, we believe are highly desirable attributes.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)